Volunteer care workers: A case for challenging resource theories on volunteering. Issue 2 (3rd April 2018) - Overgaard, Charlotte; Petrovski, Erik; Hermansen, Jonathan
ABSTRACT: This paper challenges prevailing theories on volunteering which explain participation in volunteer work by the high capital resources of individuals (resource theories). Using care theory and focusing on volunteers working with the frail elderly, the sick and the dying, we ask whether resource theory is a suitable theoretical framework for this particular kind of unpaid work. With a 2012 Danish population survey, we find that care volunteering attracts lower-resourced individuals who are predominantly female. We use this finding to argue that resource theory is unhelpful in explaining this particular form of volunteering and to call for more theory development.